1984
DOI: 10.1111/j.1469-8749.1984.tb04412.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Growth in Normal and Spastic Mice

Abstract: Longitudinal muscle growth was studied in normal and spastic mice. Muscle growth takes place at the musculotendinous junction-the 'muscle growth-plate'. In spastic mice muscle growth is reduced by 45 per cent, resulting in contractures. RESUMECroissance musculaire chez les souris normales et spastiques La croissance longitudinale du muscle a it6 etudite chez la souris normale er spastique. La croissance musculaire est sit& i la jonction musculo-tendineuse, plaque de croissance du muscle. Chez les souris spasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(51 citation statements)
references
References 21 publications
(28 reference statements)
0
48
0
3
Order By: Relevance
“…During tibial lengthening, these are not always successful, and in that setting, GSR is commonly performed before, during, or after a tibial lengthening to prevent or relieve equinus contracture [6,21]. However, the risk factors associated with gastrocsoleus contracture severe enough to warrant surgery during tibial lengthening and the consistency with which GSR results in a plantigrade foot in this setting have not been well defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During tibial lengthening, these are not always successful, and in that setting, GSR is commonly performed before, during, or after a tibial lengthening to prevent or relieve equinus contracture [6,21]. However, the risk factors associated with gastrocsoleus contracture severe enough to warrant surgery during tibial lengthening and the consistency with which GSR results in a plantigrade foot in this setting have not been well defined.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Maffulli et al [11] found an even greater threshold of 18% bone lengthening for joint contracture. The slightly higher threshold in these studies can be attributed to a pediatric population whose muscle fibers may have a greater ability to stretch and grow [6,15,21]. In a case series of 80 tibial lengthenings over an intramedullary nail, Kim et al [9] reported a 72% equinus contracture rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comparative study, longitudinal muscle growth was reduced by 45% in spastic mice, compared with normal mice. 41 This restricted longitudinal muscle growth and increased tension of the muscle can result in limb deformities, joint dislocations, and poor motor function. 42 There are many factors to consider when treating children with spasticity.…”
Section: Pediatric Considerationsmentioning
confidence: 99%
“…Affected muscles usually present with fewer myofibrils and their decreased longitudinal length. Studies have demonstrated that decrease in the longitudinal length of myofibrils of 50% leads to the onset of contractures and fixed deformities of the skeletal-joint system [4][5][6][7] . In the spastic type of CP, contractures are present in early stages.…”
Section: Introductionmentioning
confidence: 99%